Cover Picture: Enzymatic Late‐Stage Modifications: Better Late Than Never (Angew. Chem. Int. Ed. 31/2021). Issue 31 (14th June 2021) - Romero, Elvira; Jones, Bethan S.; Hogg, Bethany N.; Rué Casamajo, Arnau; Hayes, Martin A.; Flitsch, Sabine L.; Turner, Nicholas J.; Schnepel, Christian
Abstract : Biocatalytic late‐stage modifications offer attractive methods to selectively functionalise complex molecules. Amidst an ever‐growing number of enzymes, modular toolboxes of enzymatic transformations have been made available in synthesis today. Vast sets of biocatalysts are able to address manifold diversifications of interest, e.g., applied for drug development. In their Review on page 16824, Nicholas J. Turner, Christian Schnepel et al. discuss the present array of enzymatic late‐stage modification.